The Effect of Administrative Services on StudentsÔÇÖ Satisfaction - Elina Perdawati, Radia; Hafulyon, Hafulyon (Journal of Islamic Education Students (JIES), 2021)
This study aims to describe the effect of administrative personnel services on studentsÔÇÖ satisfaction. This was descriptive quantitative research that involved 110 students of state junior high schools in Solok as the sample. Data were collected using a questionnaire that was constructed based on related theories. The data analysis included testing validity, testing reliability, descriptive analysis, and simple linear regression. The findings described that there was no significant relationship between the quality of administrative services and studentsÔÇÖ satisfaction. It indicates that administrative services should pay attention to several aspects including tangibles, reliability, responsibility, assurance, and empathy to achieve studentsÔÇÖ satisfaction.┬á